PEMODELAN ARSITEKTUR ENTERPRISE MENGGUNAKAN ENTERPRISE ARCHITECTURE PLANNING UNTUK MENDUKUNG SISTEM INFORMASI AKADEMIK DI JURUSAN TEKNIK INFORMATIKA STMIK DARMAJAYA BANDAR LAMPUNG - Nisar Zaidal; Joko Triloka (Jurnal Informatika, 2008)
The way of determining information system form able to fulfil requirement of business and aligning with organizational business growth is to develop enterprise architecture. Enterprise architecture defines a process for organizing and directing information system development plan, what consist of data architecture, application architecture and technology architecture to obtain management commitments and support in integrated information system development implementation. Methodology being used in modelling this architecture is Enterprise Architecture Planning (EAP). EAP defines a process for enterprise architects that emphasize interpersonal skills and techniques for organizing and directing enterprise architecture project, obtaining management commitment, presenting the plan to management and leading the organization through the transition from planning to implementation. Research place taken as case study is Informatics Faculty at Business and Informatics Institute Darmajaya Business modelling phase is a process which create business model as representative form that defined business comprise of business function performed by enterprise. Business model used as a basic on define three architecture and making implementation plan. Result of modelling business function in Informatics Faculty at Business and Informatics Institute Darmajaya is defined counted 27 detail business function. Data architecture gets 23 data entities candidate and relationship among others. Application architecture obtains by 20 application candidate. While technological architecture yield conceptual network architecture and enterprise business system architecture.